Influence of mechanical pretreatment and organic concentration of Irish brown seaweed for methane production. (1st January 2017) - Montingelli, M.E.; Benyounis, K.Y.; Quilty, B.; Stokes, J.; Olabi, A.G.
Abstract: The European Commission opened a discussion about limiting first generation food based biofuels in favour of advanced biofuels. The main reason was to limit the uncertainty in estimates of indirect land use change emissions (ILUC) of food based biofuels. Brown seaweeds represent a valuable solution. The lack of lignin makes them suitable for degradation processes such as anaerobic digestion (AD). The main output of AD is biogas which can be upgraded to biomethane and used as a transport fuel. The most common Irish brown seaweeds namely Laminaria sp. and Ascophyllum nodosum were subject to AD. The effects of beating pretreatment time (5–10–15 min) and changes in the seaweeds volatile solids (VS) concentration (1–2.5–4%) on methane production were investigated through a response surface methodology (RSM). Laminaria sp. showed the highest methane yield of 240 ml CH4 g −1 VS when the pretreatment time was set at 15 min and at VS concentration of 2.5%. In the case of Ascophyllum nodosum, the best yield of 169 mL CH4 g −1 VS was found at the longest pretreatment time tested and at the minimum concentration of VS. The RSM analysis revealed that the VS concentration had the strongest impact on the methane yield. Highlights: Laminaria sp. exhibited 40% more methane than Ascophyllum nodosum . The VS concentration had a major impact on the methane yields of both species. The pretreatment time had a marginal impact on the methane yields of both species. Ascophyllum nodosum showed 30% more methane than the untreated sample. Laminaria sp. showed the highest methane yield at 2.5% VS and 15 min of treatment.